The limitations of Private International Law regarding the protection of unaccompanied migrant children in the European Union - Beltrame de Moura, Aline; Lerin, Carla (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This article aims to explore whether the rules of Private International Law (PIL) effectively safeguard the parental responsibility and protection of children, specifically addressing the protection of unaccompanied children migrating to the European Union (EU). The objective is to enhance the protection of the best interests of these minors. The study employs the inductive method, starting with the analysis of specific legislation and jurisprudence to derive a general premise as a conclusion. The research methodology involves bibliographic and documentary research. The findings reveal that, from a practical standpoint, PIL has limitations in its application, failing to fulfill its role in protecting the best interests of unaccompanied children in the EU.